Attachment security in infancy predicts reduced parasympathetic reactivity in middle childhood. Issue 5 (3rd September 2021) - Tabachnick, Alexandra R.; Raby, K. Lee; Goldstein, Alison; Zajac, Lindsay; Dozier, Mary
ABSTRACT: Children with histories of secure attachments during infancy are expected to develop healthier patterns of physiological activity at rest and in response to a stressor than children with insecure attachments. The present study examined longitudinal associations between infant attachment security and children's respiratory sinus arrhythmia (RSA) at rest and in response to a frustration task at age 9. The study focused on a sample of children referred from Child Protective Services ( N = 97). RSA reflects the regulation of the parasympathetic branch of the autonomic nervous system, is sensitive to environmental influences, and is associated with emotion regulation. Children with histories of secure attachments during infancy exhibited less RSA withdrawal during a frustration task than children with histories of insecure attachments. Attachment security was not significantly associated with baseline RSA. Results suggest that mitigating parasympathetic reactivity during frustrating situations may be one avenue by which infant attachment security promotes emotion regulation.